Analysis of the Dynamics of Sharia Economic Law Regulation in Indonesia - Fitriansyah, Helmi; Komaruddin, Koko (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2024)
The regulation of Sharia economic law in Indonesia reflects the government’s commitment to aligning financial and economic systems with Islamic principles. These regulations aim to foster transparency, financial stability, consumer protection, and innovation in Sharia-compliant financial products and services. This study employs a literature review approach, analyzing Indonesian legislation, regulatory updates from the Financial Services Authority (OJK), and relevant academic literature to understand the dynamics and development of Sharia economic law. The findings highlight the dynamic evolution of Sharia economic law, driven by regulatory reforms and the growth of Islamic financial institutions. Key areas of focus include advancing Sharia financial technology (fintech), enhancing Sharia financial literacy, and strengthening international cooperation. Regulatory updates by OJK emphasize transparency, accountability, and consumer protection, while fostering innovation to meet complex market demands. Despite significant progress, challenges remain in implementing oversight mechanisms and integrating technological innovations. The development of specialized regulations covering areas like waqf, zakat, and Islamic banking underscores the dynamic interaction between societal demand and regulatory responses. Sharia economic law regulations in Indonesia play a pivotal role in national economic development.Keywords: Sharia Economic Law, Regulation, Dynamics, Financial Technology.